The Repopulation of New Orleans After Hurricane Katrina - McCarthy, Kevin F. (RAND Corporation, 2006)
In November 2005, New Orleans city leaders asked RAND to estimate the repopulation of the city in the aftermath of Hurricane Katrina. The Bring New Orleans Back Commission needed estimates of the city's population in the immediate and near-term future to guide the redevelopment planning process. An assessment of flood damage to housing based on the depth of floodwater and the likely pace of reconstruction of damaged housing guided the estimates.